CONCEPTUAL METAPHORS OF EMOTION IN ADOLESCENT LANGUAGE: A COGNITIVE LINGUISTIC STUDY OF SENIOR HIGH SCHOOL STUDENTS - Tarihoran, Rezky Khoirina (SIGEH ELT : Journal of Literature and Linguistics, 2026)
This study investigates how senior high school students conceptualize emotions through metaphorical expressions from a cognitive linguistic perspective. Drawing on Conceptual Metaphor Theory, the study examines how abstract emotional experiences are structured through embodied and spatial source domains. The data were collected from 11 senior high school students using a written elicitation task covering six emotion categories: anger, sadness, fear, anxiety, happiness, and relief. Metaphorical expressions were identified using the Metaphor Identification Procedure (MIP). The findings reveal that students consistently employ a limited set of image schemas to conceptualize emotions, including CONTAINER, UP–DOWN orientation, BALANCE, and PATH/MOTION. Anger and anxiety are frequently framed through containment and pressure, sadness through downward spatial orientation, happiness through upward movement or lightness, and relief through movement toward exit or release. These patterns demonstrate that adolescents’ emotional language is systematically grounded in bodily experience rather than expressed through purely literal terms. This study contributes to emotion–metaphor research by providing empirical evidence from adolescents’ everyday language, a population that remains underrepresented in previous studies, and highlights the relevance of embodied metaphor for emotional literacy and language education in school contexts.